Melatonin: An Anti-Tumor Agent in Hormone-Dependent Cancers - Javier Menéndez-Menéndez; Carlos Martínez-Campa (International Journal of Endocrinology)
Melatonin (N-acetyl-5-methoxytryptamine) is a hormone synthesized and secreted by the pineal gland mainly during the night, since light exposure suppresses its production. Initially, an implication of this indoleamine in malignant disease was described in endocrine-responsive breast cancer. Data from several clinical trials and multiple experimental studies performed both in vivo and in vitro have documented that the pineal hormone inhibits endocrine-dependent mammary tumors by interfering with the estrogen signaling-mediated transcription, therefore behaving as a selective estrogen receptor modulator (SERM). Additionally, melatonin regulates the production of estradiol through the control of the enzymes involved in its synthesis, acting as a selective estrogen enzyme modulator (SEEM). Many more mechanisms have been proposed during the past few years, including signaling triggered after activation of the membrane melatonin receptors MT-1 and MT-2, or else intracellular actions targeting molecules such as calmodulin, or binding intranuclear receptors. Similar results have been obtained in prostate (regulation of enzymes involved in androgen synthesis and modulation of androgen receptor levels and activity) and ovary cancer. Thus, tumor metabolism, gene expression, or epigenetic modifications are modulated, cell growth is impaired and angiogenesis and metastasis are inhibited. In the last decade, many more reports have demonstrated that melatonin is a promising adjuvant molecule with many potential beneficial consequences when included in chemotherapy or radiotherapy protocols designed to treat endocrine-responsive tumors. Therefore, in this state-of-the-art review, we aim to compile the knowledge about the oncostatic actions of the indoleamine in hormone-dependent tumors, and the latest findings concerning melatonin actions when administered in combination with radio- or chemotherapy in breast, prostate, and ovary cancers. As melatonin has no toxicity, it may be well deserve to be considered as an endogenously generated agent helpful in cancer prevention and treatment.